Mechanoelectrical flexible hub-beam model of ionic-type solvent-free nanofluids. (October 2021) - Hu, Weipeng; Huai, Yulu; Xu, Mengbo; Feng, Xiqiao; Jiang, Ruisong; Zheng, Yaping; Deng, Zichen
Highlights: Presented a mechanoelectrical flexible hub-beam model of ionic-type solvent-free nanofluids. Developed a structure-preserving method for the dynamic behaviors of the ionic-type solvent-free nanofluid. Discovered the critical initial perturbation of the ionic-type solvent-free nanofluid. Abstract: The liquid-like property of solvent-free nanofluids under room temperature can be harnessed to achieve various advanced functions with significant applications. However, the determination of the critical flow conditions of solvent-free nanofluid is yet an unsolved issue. In this paper, we establish a mechanoelectrical flexible hub-beam model of ionic-type solvent-free nanofluids on the basis of microscopic mechanisms. The microscopic mechanisms of the transverse vibration of corona branches, the rotation of silica nanoparticles and the effects of the external electric field are included in this model. A structure-preserving approach, which combines the multi-symplectic method with the symplectic precise integration, is proposed to simulate the dynamics of ionic-type solvent-free nanofluids. By using this novel model, the critical initial perturbation intensity that results in the flow of an ionic-type solvent-free nanofluid is obtained, and the existence of an upper limit for the flow velocity is demonstrated, which provides a guidance for the preparation and dynamic control of ionic-type solvent-free nanofluids.